2014
DOI: 10.3109/1547691x.2014.904955
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium administration affects circulatory mononuclear cells in rats

Abstract: Although numerous investigations have demonstrated a direct effect of cadmium (Cd) on peripheral blood mononuclear cell (PBMC) activity in humans, there is virtually no data concerning the in vivo impact of this metal on circulatory mononuclear cells. In this study, the effects of a sub-lethal Cd (1 mg/kg) dose were examined in rats 48 h following a single intraperitoneal injection. Cd treatment resulted in increased total peripheral blood leukocyte levels; however, decreases in PBMC numbers were seen. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
3
6
1
Order By: Relevance
“…The reason for these differences is not clear, but show variable effects of Cd on this cytokine. Results from the present study are in line with increases in IL-1b mRNA in PBMC of rats treated with higher Cd dose (Djokic et al, 2014b) and point out this cytokine as important target for Cd. Increases in IL-1b (as well as IL-1a at higher Cd dose) underline the significance of this cytokine in Cd-induced responses in spleen.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The reason for these differences is not clear, but show variable effects of Cd on this cytokine. Results from the present study are in line with increases in IL-1b mRNA in PBMC of rats treated with higher Cd dose (Djokic et al, 2014b) and point out this cytokine as important target for Cd. Increases in IL-1b (as well as IL-1a at higher Cd dose) underline the significance of this cytokine in Cd-induced responses in spleen.…”
Section: Discussionsupporting
confidence: 91%
“…Together with our previous study that showed effect of Cd administration in rats on PBMC expression of IL-17 (Djokic et al, 2014b) data from the present study imply that IL-17 might be target for Cd.…”
Section: Discussionsupporting
confidence: 74%
“…Extensive research exploring the impact of cadmium along the inflammation axis have reported the production and upregulation of IL-6, TNF-α and IL-1β both in vivo and in vitro ( Djokic et al, 2015 ; Ninkov et al, 2015 ; Tucovic et al, 2018 ). In this study, the pro-inflammatory impact of the cadmium treatment was also observed as an upregulation in pro-inflammatory cytokines- IL-6 and IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…A later study by Djokic et al, reported differential effects of a single sub-lethal Cd dose (1 mg/kg b.w.) on rat PMN cell biology [74]. While there was a limited effect of high dose Cd on the spontaneous production of TNF-α despite an increase in the basal mRNA level, there seemed a tendency for decreased spontaneous production of IL-6 with a decrease in mRNA levels.…”
Section: Cadmium-induced Cytokine Releasementioning
confidence: 94%